Success And Failure Factors Among Jordan Microfund For Women’s Recipients Lubna - Thaher, Lubna Mohammad Naief (2022)
Over the past decades, many attempts have been made to alleviate poverty among women in Jordan through providing microcredit and facilitating financial services. Microfund for Women (MFW) is one of the most widespread, and prominent microfinance institutions in Jordan. Despite these exciting facts, many Jordanian women's enterprises funded by MFW have halted during the past decade due to the high rates of failure of these projects. Jordanian women have recently suffered from a high rate of failure in their Micro and Small-sized Enterprises (MSEs), and has gradually become an important issue following the trial of more than 13,000 Jordanian women for non-payment of their micro-loans. In order to understand further on this phenomenon while investigating how to overcome such issues, this study intends to examine the success and failure factors of women's MSEs to ensure the sustainability of their businesses, thereby empowering these women economically and socially. In this qualitative study, a semi-structured interview method with sixteen open-ended questions was used to collect data from 24 women entrepreneurs funded by MFW in Amman, Jordan. This study found three major factors for the success and failure among Jordan MFW’s recipients, namely: women entrepreneurs, the environment around women entrepreneurs, and micro-financial institutions. This study concludes with the necessity of establishing a comprehensive database for female entrepreneurs, which will guide in developing the necessary policies to promote women's entrepreneurship and thus improve their performance. This study also presented a proposed model to achieve a sustainable strategy for women's MSEs.